Participation of the state and state bodies in public law and private law relations - Suleimenоv М.К. (Bulletin of the Karaganda University “Law Series”, 2023)
he article analyzes the participation of the state in legal relations as a subject of public and a subject of private law. It is proved that in public relations the subject of law is only the state, and not state bodies, as is usually stated in the legal literature. The relations of state bodies with each other are intra-subject relations and are governed by special rules of law that are not included in the existing branches of law. With these norms, state bodies are endowed with special legal personality (only for relations between themselves). In international public relations, the state has sovereignty and immunity from prosecution. However, in international private relations, the doctrine of limited immunity operates. Kazakhstan’s attempts to preserve absolute immunity for itself are unreasonable and contrary to international treaties ratified by Kazakhstan. In internal public relations, the state is the subject of law. In private relations, the state acts as a subject of law when it is directly involved in civil law relations. State bodies can be a subject of law only when they act on their own behalf as legal entities in the organizational and legal form of a state institution.